2016
DOI: 10.1515/pjs-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of anorectal manometry in patients with a stoma before and after surgery to restore the continuity of the gastrointestinal tract

Abstract: The operation to restore the continuity of the gastrointestinal tract is another surgical intervention in a given patient, which directly translates into an increased risk of complications during and after surgery. That is why proper qualification is important for the operation to restore the continuity of the gastrointestinal tract in terms of performance and efficiency of the anal sphincter apparatus, among other things. The aim of the study was to evaluate the effect of restoring physiological defecation ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…Thus, further clinical research is necessary. Similar results have been observed by Tomasz [14] . (2) The intestinal stoma and peritubular tissue may become connected and fixed, supporting and stabilizing the tunnel colon and decreasing retraction or prolapse of the colostomy tube.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, further clinical research is necessary. Similar results have been observed by Tomasz [14] . (2) The intestinal stoma and peritubular tissue may become connected and fixed, supporting and stabilizing the tunnel colon and decreasing retraction or prolapse of the colostomy tube.…”
Section: Discussionsupporting
confidence: 92%
“…The duration from the primary operation to the restoration of gastrointestinal tract continuity may vary considerably as it depends on the tumor status, pelvic floor function and the patient’s condition. 27 The present study showed that the average time between the primary operation and the closure of the ileostomy was 171 days, which was similar to a study by Law et al (183 days). 28 Furthermore, in this study, we found that the duration of stoma ≥6 months was another independent risk factor for delayed flatus.…”
Section: Discussionsupporting
confidence: 92%
“…Two investigators (PM and MIH) independently assessed the methodological quality of the studies using the Newcastle–Ottawa Scale (NOS). 19 The scoring system covers eight items related to three major domains (selection of exposed and non-exposed cohorts, comparability and outcome assessment).…”
Section: Methodsmentioning
confidence: 99%
“…Anorectal manometry (ARM) measures the pressure in the rectum/anal canal through a pressure transducer. 19 ARM can objectively assess the quality of the continence mechanism, as it can identify functional sphincter weakness and rectal compliance and can be used to evaluate alternative procedures to stoma. 20 , 21 However, ARM technology (i.e., type of probes), methodology and protocols (i.e., timing of execution), and investigated parameters are not yet standardized in the literature.…”
Section: Introductionmentioning
confidence: 99%